PENGARUH KOMPENSASI DAN PROMOSI JABATAN TERHADAP DISIPLIN KERJA KARYAWAN - Endang Sugiarti; Mukrodi Mukrodi; I Nyoman Marayasa (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
Human resource management plays an important role for the company in order to provide maximum results while also having the best professionalism that can be relied on to achieve the company's goals and objectives, namely getting maximum profit. As the main key, human resources will determine the success of the company's activities. The demands of companies to acquire, develop and maintain quality human resources are increasingly pressing in accordance with the dynamics of the ever-changing environment. In an organization, the existence of human resources (HR) is the most important factor, so it can be seen in the reality of organizations or companies that have the same technology, work procedures and organizational structures, but the dynamics or mobility of organizations or companies differ from one another. . This study aims to determine the effect of compensation and promotion on employee performance at PT. Lasting Era Brilliant Thamrin Residence Branch